How Did EU Membership of Eastern Europe Affect Student Achievement? - Annika B. Bergbauer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The accession of Eastern European countries to the European Union increased family wealth and the returns to schooling. I analyze the change in student achievement due to the EU accession of Eastern Europe building on a panel of six PISA waves covering more than 1 million students in 32 countries. Using a difference-in-differences approach I find a positive and statistically significant link of EU membership to reading scores by one decile of a standard deviation. Mediation analysis suggests school efficiency, family wealth, and family structure as key transmitters of EU membership to student achievement.
Keywords: I28; H52; L15; D82; P50; 330; European Union; student achievement; PISA